パッチ畳み込みニューラルネットワークを用いる癌分類 (2023)
被験体の生物学的試料から核酸のメチル化シーケンシングによって決定される断片のメチル化パターンのデータセットを得ることを含む、種の被験体の疾患状態を決定するための方法が提供される。断片のメチル化パターンは、断片中の各ＣｐＧサイトのメチル化状態を含む。パッチによって表される参照ゲノム中のＣｐＧサイトのセットにおけるそれぞれのＣｐＧサイトのメチル化状態のパラメータを備えるチャンネルを含むパッチは、ＣｐＧサイトのセットに並ぶ複数の断片中のそれぞれの断片について、それぞれの断片のメチル化パターンに基づいて複数のパラメータの全部または一部のインスタンスをポピュレーションすることによって構築される。パッチ回帰ニューラルネットワークへのパッチの適用は、被験者の疾患状態を決定する。 Methods for determining a disease condition of a subject of a species are provided that comprises obtaining a dataset of fragment methylation patterns determined by methylation sequencing of nucleic acid from a biological sample of the subject. A fragment methylation pattern comprises the methylation state of each CpG site in the fragment. A patch including a channel comprising parameters for the methylation status of respective CpG sites in a set of CpG sites in a reference genome represented by the patch is constructed by populating, for each respective fragment in the plurality of fragments that aligns to the set of CpG sites, an instance of all or a portion of the plurality of parameters based on the methylation pattern of the respective fragment. Application of the patch to a patch convolutional neural network determines the disease condition of the subject.